The Impact of Acquisition on Financial Performance: The Case of Manufacturing Companies in Indonesia - Ramadian, Nidia Pasha (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research is to examine the impact of acquisition on financial performance of manufacturing companies in Indonesia. The study uses manufacturing companies listed in the Indonesia Stock Exchange from 2010-2013 as the samples. While, variables used in this research are financial ratios including liquidity ratio, activity ratio, leverage ratio, and profitability ratio. The financial performance is analyzed using financial ratios consists of liquidity ratio, activity ratio, leverage ratio, and profitability ratio. To find out the relationship between the variables paired t-test analysis is applied. Finally, the financial ratio analysis result shows that there is no significant difference between one year before and after acquisition, only quick ratio that undergoes significant change. From the result it could be assumed that acquisition generally don’t significantly influence the financial performance of the acquirer company with financial ratio by proxy. This could happen because there might be weak strategies and the lack of experiences in doing acquisition. Keyword: Acquisition, Financial Performance of Company, Financial Ratio